A neurorobotic platform to test the influence of neuromodulatory signaling on anxious and curious behavior - Krichmar, Jeffrey L. (Frontiers in Neurorobotics, 2013)
The vertebrate neuromodulatory systems are critical for appropriate value-laden responses to environmental challenges. Whereas changes in the overall level of dopamine have an effect on the organism’s reward or curiosity seeking behavior, changes in the level of serotonin can affect its level of anxiety or harm aversion. Moreover, top-down signals from frontal cortex can exert cognitive control on these neuromodulatory systems. The cholinergic and noradrenergic systems affect the ability to filter out noise and irrelevant events. We introduce a neural network for action selection that is based on these principles of neuromodulatory systems. The algorithm tested the hypothesis that high levels of serotonin lead to withdrawn behavior by suppressing dopaminergic action and that high levels of dopamine or low levels of serotonin lead to curious, exploratory behavior. Furthermore, the algorithm tested the idea that top-down signals from the frontal cortex to neuromodulatory areas are critical for an organism to cope with both stressful and novel events. The neural network was implemented on an autonomous robot and tested in an open field paradigm. The open field test is often used to test for models anxiety or exploratory behavior in the rodent and allows for qualitative comparisons with the neurorobot’s behavior. The present neurorobotic experiments can lead to a better understanding of how neuromodulatory signaling affects the balance between anxious and curious behavior. Therefore, this experimental paradigm may also be informative in exploring a wide range of neurological diseases such as anxiety, autism, attention deficit disorders, and obsessive-compulsive disorders.